2014
DOI: 10.1093/aobpla/plu033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light on the growth and photosynthesis of an invasive shrub in its native range

Abstract: We studied the growth and photosynthetic capacity of Berberis darwinii shrub growing under different light conditions in their native area of Argentina to test if plant physiology differs from invaded area (using studies carried out in New Zealand). In its native range B. darwinii grows under different light conditions by adjusting shoot and leaf morphology and physiology. Plants of B. darwinii growing under the same light environments show similar physiology in native and invasive ranges. Therefore, intra-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
5
3
0
1
Order By: Relevance
“…Therefore, under shade conditions B. darwinii plants assign the carbon fixed to vegetative growth and, when light quantity and quality reaches to at least an edge plant level, favourable conditions for the development of reproductive organs would be generated since the increment in photosynthesis would lead to reproduction allocation. This concurs with the higher maximum photosynthesis in plants growing on the forest edge than in those under the forest canopy found by Svriz et al (2014). A similar response also takes place in grasslands after disturbances such as fire, where suppressed species develop reproductive organs due to the increase of light availability and the removal of biomass (Lamont & Downes, 2011; Goldas et al, 2022).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, under shade conditions B. darwinii plants assign the carbon fixed to vegetative growth and, when light quantity and quality reaches to at least an edge plant level, favourable conditions for the development of reproductive organs would be generated since the increment in photosynthesis would lead to reproduction allocation. This concurs with the higher maximum photosynthesis in plants growing on the forest edge than in those under the forest canopy found by Svriz et al (2014). A similar response also takes place in grasslands after disturbances such as fire, where suppressed species develop reproductive organs due to the increase of light availability and the removal of biomass (Lamont & Downes, 2011; Goldas et al, 2022).…”
Section: Resultssupporting
confidence: 92%
“…Besides, low temperatures also decrease the production of floral organs (Southwick, 1984; Zhang et al, 2015). In addition to the differences in canopy openness registered in this study, Svriz et al (2014) also found lower temperatures under the forest canopy in respect to gap and forest edges.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Una mayor apertura de dosel se correspondió con mayor probabilidad de fructificación y número de frutos por planta. Una tendencia similar fue descripta por Svriz et al (2014), quienes observaron que el michay (B. darwinii) florece sólo en los claros del bosque. Otras especies frutícolas silvestres, como el arándano silvestre (Vaccinium myrtillus) y la rosa multiflora (Rosa multiflora) también se comportan de esta forma (Dlugos et al 2015;Eckerter et al 2019).…”
Section: D��������unclassified
“…Sites with a higher maximum PAR were more likely to have reproductive buckthorn plants present as well. Similarly, Darwin's barberry (Berberis darwinii) is an invasive tree that does not produce flowers when under a canopy due to decreased light conditions (Svriz et al 2014). The brightest sites, therefore, supported the most buckthorn biomass (both live and dead), reproductive individuals, and the oldest plants.…”
Section: Light Availability and Its Influence On Buckthornmentioning
confidence: 99%